THE EFFECT OF EXCHANGE RATES ON EXPORTS AND IMPORTS OF EMERGING COUNTRIES - Genc, Elif Guneren; Artar, Oksan Kibritci (European Scientific Journal, ESJ, 2014)
The debate regarding the desirable degree of foreign exchange rate policies hasbeen persisting for decades. Markets are able to effectively achieve optimum efficacy and maximize welfare output when operated without distortions. This research was guided by two key objectives;to determine the impact of exchange rates on imports and to investigate the impact of exchange rates on exports of economically developing countries. This paper focusses on establishing whether there is a co-integrated relationship between effective exchange rates of selected emerging countries. Many studies have indicated that policies touching on exchange rates closely affect the international trade of a country. This study applies the panel cointegration method for the period of 1985-2012. The annual data used in the empirical analysis were obtained from the World Bank data base. As a result, there is co- integrated relationshipbetween effective exchange rates and exports-imports of emerging countriesin the long run.